PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL (IPS) KELAS IV SDN 012 RANTAU BAIS KECAMATAN TANAH PUTIH - Masdalifah '; Gusnardi '; RM. Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: Education not only as a conduit of information knowledge and skillsformation, but broader than that. Which includes efforts to realize the desires, needsand abilities of the individual in order to achieve personal and social life patternssatisfactory, not merely as a means to prepare people for life in the future but also forthe lives of children today who are undergoing development towards maturity level.Cooperative learning implies as an attitude or behavior in work or help among othersin the same regular structural work in groups of two or more persons where theemployment success is strongly influenced by the involvement of each member of thegroup it self. Group Investigation is a discovery made in groups: pupils / students ingroups to experience and experiment with active which allows finding principles. Thepurpose of this study presented is to improve learning outcomes IPS Students in gradeIV SDN 012 districts Rantau Bais White Rokan Hilir land through cooperative learningmodel type Group Investigation. Points penelian done in SDN 012 Rantau Bais Putihsubdistrict soil Rokan Hilir. Samples of research that students of class IV. Datacollected by using learning outcomes and non-test techniques. Techniques used toanalyze the thoroughness of the individual, classical, teachers and students andtechnique improving student learning outcomes. From the analysis done shows thatimplementation of cooperative learning model of Group Investigation can improvelearning outcomes math grade IV SDN 012 Rantau Bais Tanah Putuh Rokan Hilir.Keywords: Group Investigation Model , Interest to learn